Stem-ethnoscience learning improves elementary students' critical thinking - Rahmat Hidayat; Setyo Eko Atmojo; Mitha Dwi Anggriani; Tommy Tanu Wijaya (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2026)
This study aims to analyse the effect of implementing STEM-based science learning integrated with ethnoscience on critical thinking skills of elementary school students. This research is based on the importance of mastering critical thinking skills as one of the 21st-century competencies that must be developed since the elementary school level, as well as efforts to link science learning with the local cultural context through ethnoscience. The research method used was a pseudo-experiment with a pretest-posttest control group design. The research instrument was a validated critical thinking skills test. Data analysis was conducted using prerequisite tests (normality and homogeneity) and hypothesis testing with a paired-samples t-test and an independent-samples t-test using SPSS 25. The results showed that there was a significant increase in critical thinking skills in students who participated in STEM-ethnoscience-based learning compared to students who participated in conventional learning. The application of STEM-ethnoscience provides a more meaningful learning experience because it connects science concepts with local cultural practices. Thus, it can be concluded that STEM learning integrated with ethnoscience is effective in improving critical thinking skills of elementary school students and has the potential to become an innovative model in the development of culture-based science learning in the 21st-century education era.